SPIRITUALITAS DAN KESUKSESAN BELAJAR: Studi Meta Analisis - Ghufron, M Nur (Program Studi Pendidikan Agama Islam, 2016)
SPIRITUALITY AND LEARNING SUCCESS: META ANALYSIS STUDY. This Study used meta-analysis of the relationship between spirituality and learning success. Meta-analysis aimed at concluding, integrating, and interpreting data gathered from previous research. Therefore, this sreseach was apart from acting as primary research. The data was analyzed through this method must have the same constructs and correlation patterns so that it could be compared with one another. The quantitative review included 14 studies from 15 articles that contained a combined sample of approximately 3119. This analysis extended previous work by directly correcting error of sampling and measurements. Summary analysis provided support that had a correlation on learning success spirituality. The result showed that spirituality has been identified as predictors and learning success.